A lógica interna dos orçamentos da Universidade Federal de Santa Maria: uma perspectiva institucional - Morais, Zaloar Cunha de (2022)
The managerial autonomy of public universities is guaranteed by article 207 of the Federal Constitution makes the established forms of internal budgets organization an important issue for the stakeholders of the Federal University of Santa Maria. The description of the conflicts of institutional adaptation of UFSM internal budgeting practices about dominant budgetary logic can help managers and the university community to change established forms for their benefit. The purpose of this dissertation is to understand tensions produced by the confrontation between UFSM's internal dominant budget logic and the budget field logic restricted to eight hypotheses taken from legal and literary cognitive components. The research uses the abductive method to describe the dominant internal logic of UFSM budgets based on document analysis of Statutes, Minutes, and resource distribution proposals and, testing of a means of averages applied to programming and budget execution data. The dominant logic of the UFSM internal budgets can be described as incremental, by formulas and controlling of inputs with programmatic elements weakly coupled to the budget. Despite tax pressure and political crises, the internal logic underlying the budget process remains stable based on the centralization of decisions and the protection of appropriations legitimized by the high percentage of the expenditures committed.